2017
DOI: 10.1080/14789949.2017.1396487
|View full text |Cite
|
Sign up to set email alerts
|

The use of telepsychiatry within forensic practice: a literature review on the use of videolink – a ten-year follow-up

Abstract: In the last decade telepsychiatry -the use of telecommunications technologies to deliver psychiatric services from a distance -has been increasingly utilised in many areas of mental healthcare. Since the review by Khalifa and colleagues in 2007 the body of literature relevant to the forensic applications of telepsychiatry has grown substantially, albeit not by much in the United Kingdom.In the current review we aim to provide an update summary of the literature published since 2007 to determine the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 30 publications
4
51
0
Order By: Relevance
“…non-intellectual disability) mental health services. [19][20][21][22] These, however, do not focus on the key issues encountered by the intellectual disability patient group and the specialist psychiatric services that serve them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…non-intellectual disability) mental health services. [19][20][21][22] These, however, do not focus on the key issues encountered by the intellectual disability patient group and the specialist psychiatric services that serve them.…”
Section: Introductionmentioning
confidence: 99%
“…Several innovative telepsychiatry services have been developed for use in adult, forensic, and child and adolescent mainstream (i.e. non-intellectual disability) mental health services 19 22 . These, however, do not focus on the key issues encountered by the intellectual disability patient group and the specialist psychiatric services that serve them.…”
Section: Introductionmentioning
confidence: 99%
“…Both patients and services are increasingly accepting of the use of video links in forensic mental healthcare. 7 However, the acceptability of telepsychiatry may vary according to individual patients’ preferences, needs and underlying mental disorder(s). Tucker et al found that, although prisoners preferred face-to-face assessments, remote consultations were preferred for discussing difficult topics such as sexual abuse.…”
Section: Acceptability To Patients and Cliniciansmentioning
confidence: 99%
“…Benefits have been shown in criminal justice and other forensic settings, where safety concerns about physical movement of high-risk patients can be mitigated through remote assessments and remote expert testimony. 17 Remote psychiatry has also been demonstrated to have a positive impact on the assessment and management of individuals with intellectual disabilities, with some data showing no loss in therapeutic engagement compared with face-to-face assessments and even some evidence for improved engagement among children with severe anxiety and autism. 18 In addiction psychiatry, remote treatment of opioid use disorder produced similar outcomes as face-to-face treatment in both general 19 and obstetric settings.…”
Section: Is Digital Psychiatry Safe Effective and Acceptable To Patimentioning
confidence: 99%